A Modern Approach Towards Istihsan - Haji Mahamad Naser, Disa; Akmal, Mohamad (2019)
Istihsan is not a new source of law. It is not a concept which stems from the sole exercise of one’s conscience. Istihsan can sometimes be applied incorrectly due to misplaced prioritization. Whilst the concept of Istihsan is wide, its proper implementation should never go against clear injunctions by the primary sources. An approach which prioritizes any subjective social values over clear prohibitions and admonitions found in the al-Quran and as-Sunnah are unsustainable. The objective of this paper to discuss the role of Istihsan as well as misconception of its role whereby it was cloaked by other secondary sources especially Maslahah or Masalih al-Mursalah or even Siyaasah as-Shar’iyyah. This is a doctrinal research. It concludes that in the era of globalization and technological advancement, the role of Istihsan seems to be more relevant and important.